Anthropogenic dynamics and recovery of disturbed landscapes at the Far East Russia permafrost area - Tikhmenev Pavel E.; Smirnov Andrey A.; Tikhmenev Evgeniy A.; Stanchenko Galina V. (E3S Web of Conferences, 2020)
The results of studies of anthropogenic landscapes functioning with an assessment on the processes of natural self revegetation are summarized. The principles of accelerated restoration of the ecological and aesthetic value of disturbed landscapes at the permafrost zone are substantiated, based on the data obtained during studying the selfrevegetation processes on disturbed complexes. Development of placer and ore deposits of mineral resources is leading to deep transformation of landscape and to destruction of soil-vegetable complexes. The processes caused by mining-technical activity are leading to variable mechanisms of degradation of soil and vegetables often having complex impact. Results of study of sustainability of soil-vegetable complexes to the impact of mancaused activity have showed the dependence from the structure of the soil profile and it characteristic, from the character of genetic horizons, frozen status of the landscape elements, form the structure and biomass and productivity of vegetation cover.